ANALISIS KENAKALAN REMAJA PADA PESERTA DIDIK KELAS VIII SMP NEGERI 3 PONTIANAK - Bahri, Saiful; Yuline, Yuline; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrackJuvenile delinquency in schools with various forms including ditching, chatting during class hours, running away from school during class hours, smoking, not doing homework, not wearing belts and socks, often late coming to school, cheating, and dating. Therefore researchers want to know more deeply about juvenile delinquency in students in class VIII SMP Negeri 3 Pontianak. The problem in this study is "How is juvenile delinquency in grade VIII students of SMP Negeri 3 Pontianak?". This study aims to determine juvenile delinquency in grade VIII students of SMP Negeri 3 Pontianak. The method used is descriptive method in the form of survey research studies. The sample of this study was 43 students of class VIII of SMP Negeri 3 Pontianak. This study uses a quantitative approach. The data collection technique of this research is the indirect communication technique with a questionnaire data collection tool. The data analysis technique uses percentage calculation. Based on the results of the analysis of juvenile delinquency data in class VIII students of SMP Negeri 3 Pontianak reached 80.56% with the category "very high". While the impact of juvenile delinquency reached 82.02% with the category "very high". And the effort to handle by BK teachers on juvenile delinquency reached 81.60% with the "very high" category.Keywords: Juvenile, Delinquency.